Analisis Penerapan Prinsip Penyajian Dan Pengungkapan Standar Akuntansi Keuangan Tentang Kombinasi Bisnis Pada Laporan Keuangan Pt Astra International Tbk Periode 2020-2022 - Endang Kartini Panggiarti; Fanny Fauziah; Agnes Zerlinda Bella Nathania; Elvira Ayu Lestari (Pusat Riset dan Inovasi Nasional, 2024)
The financial condition of a company is accurately and transparently reflected in its financial statements, so the company needs to pay attention to the principles of Financial Standards (SAK) in business combinations. The presentation and recognition of goodwill by PT Astra International Tbk. must comply with applicable financial accounting standards, in order to create good financial statements and facilitate users in understanding the contents of the financial statements. The purpose of this study is to find out how PT Astra International Tbk. applies the principles of presentation and disclosure of financial accounting standards in its financial statements for business combinations. The data collection method used in this study is secondary data in the form of consolidated reports for the period 2020 to 2022. The results of this study indicate that the presentation of PT Astra International Tbk's financial statements has complied with generally applicable standards and has presented the results of business combination activities in the form of goodwill recording by PT Astra International Tbk amounting to Rp824 billion in its financial statements.